Bio-diversity Conservation and Eco-tourism: A Case Study from Lang National Park - Shrestha, Uttam Sagar (Himalayan Review, 2011)
Available with fulltext. Key words: Ecosystem; Bio-diversity; Eco-tourism; New approach The Himalayan Review Nepal Geographical Society Vol. XXXII 2001 Page: 41-54 Uploaded date: 7 June, 2011